2008
DOI: 10.1007/s00192-008-0669-9
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological analysis of the urogenital diaphragm in elderly women: a cadaver study

Abstract: The objective of this study was to describe the histomorphological structure of the urogenital diaphragm in elderly women using a modern morphometric procedure. Biopsies were taken from the posterior margin of the urogenital diaphragm of 22 female cadavers (mean age, 87 years) using a 60-mm punch. Hematoxylin/eosin and Goldner sections were analyzed with the Cavalieri estimator. The mean thickness of the urogenital diaphragm was 5.5 mm. The main component was connective tissue. All biopsies contained smooth mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Histological evidence for all of these structures has been provided in the form of photos in this review. Likewise, for measurement of thickness using clinical imaging, Betschart et al [87] considered the perineal membrane as en mass that includes striates muscle, smooth muscle, and connective tissues. Because the deep transverse perineal muscle is sometimes thick and wide, even in elderly men [63] (Figure 5(a)), we do not need to rule out the concept of the urogenital diaphragm.…”
Section: Methodsmentioning
confidence: 99%
“…Histological evidence for all of these structures has been provided in the form of photos in this review. Likewise, for measurement of thickness using clinical imaging, Betschart et al [87] considered the perineal membrane as en mass that includes striates muscle, smooth muscle, and connective tissues. Because the deep transverse perineal muscle is sometimes thick and wide, even in elderly men [63] (Figure 5(a)), we do not need to rule out the concept of the urogenital diaphragm.…”
Section: Methodsmentioning
confidence: 99%
“…5). Thus, conversely, we did not evaluate whether or not the lateral extension of the PM 14 was attached to the bony pubic ramus. We tried to classify the PM into a thick and thin group (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The rectovaginal septum joins the ligament to form the arcus tendineus fasciae pelvis 8–10 . Recently, the morphology of the perineal membrane or level 3 support has also been described in detail 11–14 . The tissue architecture and components vary between nulliparous and multiparous women 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…The present study clearly demonstrated the topographical relationship of the elastic fiber-rich smooth muscle-poor PM with the inferomedial edge of the levator ani muscle. Although various amounts of smooth muscle have been reported in the PM [13], these might have represented the lateral or superior part. Previous data on the thickness of the PM (mean, 5.5 mm) [13] had suggested that it was much thicker than in the present series of specimens (5.5 mm at maximum), but this difference may have simply been attributable to the definition employed, i.e.…”
Section: Discussionmentioning
confidence: 99%